PROSEDUR KLAIM JAMINAN HARI TUA (JHT) PADA BPJS KETENAGAKERJAAN - Mirnawati, Mirnawati (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2023)
The purpose of the research is to find out the old-age security claim system, the implementation of the old-age security claim system and the effectiveness of the old-age security claim system. The research method that the author uses in this research is descriptive analysis, with the research approach used in this research being qualitative. The results showed that the old-age security (JHT) claim system is one form of service provided by the Social Security Administration (BPJS) of Employment to provide social protection guarantees for participants who have reached retirement age and meet the JHT claim requirements. The JHT claim system at BPJS Ketenagakerjaan is implemented by following predetermined procedures. Namely, participants must first register and pay JHT contributions regularly for at least 15 years before they can submit JHT claims. The JHT claim process is done by applying online or directly to the nearest BPJS Ketenagakerjaan office by attaching the required supporting documents. After verification and data processing, BPJS Ketenagakerjaan will disburse claim funds to participants. The effectiveness of the JHT claim system can be measured by how fast, easy, and accurate BPJS Ketenagakerjaan is in providing services to participants. In this case, BPJS Ketenagakerjaan must be able to provide timely and efficient services so that participants do not experience difficulties when submitting JHT claims. In addition, BPJS Ketenagakerjaan must also be able to deliver quality solutions and services if there are problems or complaints from participants regarding the JHT claim process.